HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TERHADAP KEIKUTSERTAAN PELAYANAN KONSELING GIGI DI PUSKESMAS KABUPATEN HULU SUNGAI UTARA - Rista Amalia Pratiwi; Rosihan Adhani; Karina Ramadhani (FKG Unlam, 2017)
ABSTRACTBackground: Knowledge is the foundation for a development of human behavior, especially health behavior. Health behavior is activity of humankind to maintain and improve their health. One of these actions is included in the dental counseling service in the society. In Hulu Sungai Utara regency, the participation in the dental counseling service is quite low, around 5,3%, that is why some researches need to be done in this area. Purpose: This study aimed to find out the relation between the rate of knowledge in the society and the participation in the dental counseling service at Puskesmas Hulu Sungai Utara. Method: This research is an analytical observation stud, with cross sectional advance. There were 150 respondents for this study, with each Puskesmas provided 50 respondents. The rate of knowledge in the society and the participation in the dental counseling service were measured by questionnaire. Result: There were 61 respondents who had low rate of knowledge, 75 respondents who had intermediate rate of knowledge, and 14 respondents who had high rate of knowledge. There were 100 respondents who had low rate of dental counseling participation, 21 respondents who had intermediate rate of dental counseling participation, and 29 respondents who had high rate of dental counseling. Chi-Square test showed that the rate of knowledge in the society is related with the participation on dental counseling service. The test of the data showed significant score (p<0,05). Conclusion: The conclusion of this study presented that dental counseling service participation is affected by the knowledge of the society.Keywords: health behavior, knowledge, dental counseling service